Genealogi Manhaj dan Ittijāh Penafsiran al-Shawkāny dalam Kitab Tafsir Fatḥ al-Qadīr - Saputro, Oscar Wardhana Windro (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2024)
This research is aimed at finding out the genealogy of the manhaj and ittija>h interpretations of al-Shawka>ny in the book of tafsir Fath} al-Qadi>r. Judging from the research location, type of data and research sources, this research has a qualitative research approach with the type of library research. The data sources in this research, apart from the book of interpretations of Fath} al-Qadi>r, are other books by al-Shawka>ny, as well as al-Shawka>ny's biography to get a description of life and the society around him which influenced his thinking and approach. understand the interpretation of the Koran. Al-Shawka>ny is considered a breakthrough with his thoughts which sought to free society from blind fanaticism towards one particular school of thought. After conducting research, it can be concluded that the manhaj and ittija>h interpretations of al-Shawka>ny in the book of tafsir Fath} al-Qadi>r tend to follow the interpretation methods of classical commentators such as al-Qurt}uby, al-Suyut}y, Ibn Kathi >r, al-Baghawy and Ibn Jari>r al-T{abary. The new finding obtained is Manhaj's interpretation of al-Shawka>ny in the book of tafsir Fath} al-Qadi>r, if seen from the source of the interpretation, it uses the tafsir bi al-Iqtira>n method. If we look at the systematics of the explanation, it uses systematic muqa>rin or comparative interpretation. The breadth of interpretation is the It}na>by interpretation method. Meanwhile, according to the target and sequence of the verses, it is the Tah}li>ly method of interpretation. Ittija>h interpretation of al-Shawka>ny in the book of Tafsir Fath} al-Qadi>r, of which there are several styles that dominate apart from Tafsir Lughawy, namely Tafsir Aqady and Tafsir Fiqhy. Even though al-Shawka>ny combines the methods of tafsir bi al-Ma'thu>r and tafsir bi al-Ra'y, the direction of his interpretation tends to be conservative textualist because he adheres strictly to athar, the interpretation of classical commentators and Arabic. The results of this research are useful in determining the classification of al-Shawka>ny's tafsir books as well as providing input for other researchers regarding al-Shawka>ny's thoughts and interpretive manhaj and ittija>h in general.